Effect of Paclobutrazol Concentration and Urea Fertilizer Dosage on Plant Growth and Yield Long Beans (Vigna sinensis L.) - Djarwatiningsih, Djarwatiningsih; Sulistyono, Agus; Safitri, Novita Dyah (The University of Lampung, 2024)
Long bean is a well-known horticultural commodity in people's lives with quite high nutritional value. This study aims to determine the effect of paclobutrazol concentrations and doses of Urea fertilizer on the growth and yield of long bean plants. Long bean plants were planted on private cultivation land in Werungotok Village, Nganjuk District, Nganjuk Regency, East Java in January 2023 – April 2023. The study was structured using a Split Plot Design with 2 factors, including concentration of paclobutrazol and the dose of Urea fertilizer. Each factor consisted of 4 levels and was repeated 3 times. The results revealed that the concentration of paclobutrazol and the dose of urea fertilizer had an effect on plant length, number of leaves, age of flower emergence, number of flowers, number of fruits, fruit weight per plant, fruit weight per plot, fruit weight per hectare, fruit length and fruit set. The best results were obtained from the treatment with a concentration of 150 ppm paclobutrazol and a dose of 100 kg/ha of urea. Keywords: Growth, Paclobutrazol concentration, Urea dose, Yield.